2021
DOI: 10.1002/jee.20412
|View full text |Cite
|
Sign up to set email alerts
|

Engineering student perceptions of social justice in a feedback control systems course

Abstract: Background Although engineering practice occurs in social contexts, such contexts often remain obscure in engineering education. Since engineering sciences courses are crucial in shaping engineering students' knowledge and conceptions of problem‐solving in engineering, students in both an augmented and a traditional section of a feedback control systems course were interviewed to explore perceptions of the social justice dimensions of engineering. Purpose This study sought to understand student perceptions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 50 publications
2
33
0
Order By: Relevance
“…Different methodologies could be applied to analyze academic programs, such as interviews with students, academic stuff or other actors involved in the curriculum [23], as well as in-depth analysis of the curriculum [24]. Navarro et al [25] suggested using the consistency value calculated with the AHP technique [26] to assess the critical thinking of master's degree students.…”
Section: Methodsmentioning
confidence: 99%
“…Different methodologies could be applied to analyze academic programs, such as interviews with students, academic stuff or other actors involved in the curriculum [23], as well as in-depth analysis of the curriculum [24]. Navarro et al [25] suggested using the consistency value calculated with the AHP technique [26] to assess the critical thinking of master's degree students.…”
Section: Methodsmentioning
confidence: 99%
“…Leydens, Lucena, and colleagues (Leydens & Lucena, 2014; 2018; Leydens et al, 2021) have introduced principles for humanitarian engineering, service learning, and social justice via the “Engineering for Social Justice (E4SJ)” framework. Students are taught about the social contexts of engineering and design, sociotechnical systems, and the agency of engineers, designers, and stakeholders in creating just or unjust outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Students are taught about the social contexts of engineering and design, sociotechnical systems, and the agency of engineers, designers, and stakeholders in creating just or unjust outcomes. Leydens et al (2021) argue that “students are more likely to value social justice concepts when they are presented within the context of—and as highly relevant to—solving engineering problems,” and that “faculty should acknowledge that social justice considerations are already inherent in such problems, both in their formulations and solutions” (p. 741).…”
Section: Introductionmentioning
confidence: 99%
“…The future of mining and other natural resource industries will require engineers who can take a sociotechnical approach to the challenges they face and the decisions they make in their working lives. The term sociotechnical recognizes that issues that appear to be technical in nature have an inherent social dimension [1][2][3]. For example, the coming energy transition will require massive amounts of minerals and metals, from the copper and iron necessary for power generation, transportation, and use, to the lithium, cobalt, and nickel required for electric vehicles.…”
Section: Introductionmentioning
confidence: 99%